Edukasi dan Pendampingan Penerapan Perilaku “BORIA” dalam Upaya Penurunan Kejadian Diabetes Melitus di Desa Genaharjo Kec. Semanding Kab. Tuban - Nur Cahyani, Nabila; Puspitadewi, Teresia Retna; Cahyani, Mirna Tri; Nurjanah, Noviatul; Azaro, Devia Fatimatus; Irianti, Dhevina Yogi Ara (Jurnal Ilmiah Tatengkorang, 2025)
In the era of globalization, which is where there is a global era, there is a shift from infectious diseases to non-communicable diseases such as the emergence of more and more degenerative diseases, one of which is Diabetes Mellitus (DM). Diabetes mellitus is one of the diseases that are most suffered by the Indonesian people. This disease is called a silent killer because patients are often unaware so they are prone to complications Diabetes mellitus has the main cause, namely an unhealthy lifestyle. On the other hand, the people of Genaharjo Village, Semanding District, Tuban Regency have a habit of drinking coffee, staying up late, and among others obesity. This is the basis for the implementation of the student creativity program by providing an overview and explanation related to diabetes mellitus, the implementation of healthy living behaviors with the "BORIA" program and "BORIA" gymnastics assistance. As a result of holding this program, the majority of the elderly have almost all implemented the "BORIA" program as many as 15.4 (77%). It is hoped that this program can help the community in Genaharjo Village in an effort to control and prevent complications due to diabetes mellitus Sejumlah penyakit tidak menular, seperti meningkatnya prevalensi penyakit degeneratif seperti Diabetes Melitus (DM), telah menggantikan penyakit menular di era globalisasi ini. Salah satu penyakit yang paling umum di Indonesia adalah diabetes melitus, yang dianggap dapat menimbulkan sejumlah komplikasi dan penyakit serius. Pasien sering kali tidak menyadarinya, sehingga mereka rentan terhadap konsekuensinya, itulah sebabnya penyakit ini disebut sebagai pembunuh diam-diam. Penyebab utama diabetes melitus adalah gaya hidup yang tidak sehat. Di sisi lain, masyarakat Desa Genaharjo Kecamatan Semanding Kabupaten Tuban memiliki kebiasaan minum kopi, begadang, dan diantaranya obesitas. Hal tersebut yang mendasari pelaksanaan program kreativitas mahasiswa dengan memberikan gambaran dan penjelasan terkait diabetes melitus, penerapan perilaku hidup sehat dengan program “BORIA” serta pendampingan senam “BORIA”. Hasil diadakannya program ini, mayoritas lansia hampir seluruhnya telah menerapkan program “BORIA” sebanyak 15,4 (77%). Harapannya program ini dapat membantu masyarakat di Desa Genaharjo dalam upaya mengendalikan dan mencegah terjadinya komplikasi akibat diabetes melitus.